Inovasi Pelayanan Publik Berbasis Aplikasi Excise Services Information System (Exsis) di Kantor Pengawasan dan Pelayanan Bea dan Cukai Sidoarjo - Yulafreean Dwi Andianto; Aris Sunarya; Nihayatus Sholichah; Sri Roekminiati; Sapto Pramono (Journal of Management and Social Sciences, 2025)
This study discusses the implementation of the Excise Services Information System (ExSIS) application at the Sidoarjo Customs and Excise Office as an innovation in public services. The objective is to evaluate the effectiveness of ExSIS in improving operational performance and provide recommendations for its development. This research employs a qualitative method with interviews conducted with Customs and Excise officers and service users, analyzed using Everett M. Rogers' diffusion of innovation theory. The results indicate that ExSIS improves time efficiency by up to 80% and reduces administrative errors by 70%. However, challenges such as user adaptation and the need for adequate infrastructure remain. In conclusion, ExSIS has enhanced efficiency and transparency in Customs and Excise administration. The study recommends continuous training, infrastructure upgrades, and internal policy revisions to maximize the application’s potential in supporting faster and more accurate public services.